2016
DOI: 10.4064/bc110-0-11
|View full text |Cite
|
Sign up to set email alerts
|

Nonabelian omni-Lie algebras

Abstract: We introduce the notion of a nonabelian omni-Lie algebra associated to a Lie algebra. From a geometric point of view, it is the linearization of the Courant algebroid associated to a Poisson manifold. As an algebraic application, we show that its Dirac structures describe deformations of the Lie algebra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…On the other hand, by Theorem 4.6, the generalized complex structure J will also induce a Lie algebroid structure on E by (13). By the equality…”
Section: Generalized Complex Structures On Omni-lie Algebroidsmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, by Theorem 4.6, the generalized complex structure J will also induce a Lie algebroid structure on E by (13). By the equality…”
Section: Generalized Complex Structures On Omni-lie Algebroidsmentioning
confidence: 95%
“…• Given a crossed module of Lie algebras (m, g), we get an m-Courant algebroid Hom(g, m) ⊕ g, which was given in [13] as a generalization of an omni-Lie algebra.…”
Section: Introductionmentioning
confidence: 99%
“…一个非交换的 omni-李代数可以看成由 Poisson 流形给出的 Courant 代数胚的线性化, 也可以看 成 omni-李代数的平凡形变, 有丰富的代数和几何性质. 更多内容参见文献 [28].…”
Section: Omni-李代数unclassified
“…In [19], the authors introduced the notion of a nonabelian omni-Lie algebra (gl(g) ⊕ g, (·, ·) + , {·, ·} g ) associated to a Lie algebra (g, [·, ·] g ), which originally comes from the study of homotopy Poisson manifolds [18]. In particular, they showed that it is the linearization of the Courant algebroid T g * ⊕T * πg g * associated to the linear Poisson manifold (g * , π g ), where π g is the Lie-Poisson structure on g * .…”
Section: Introductionmentioning
confidence: 99%